Desain dan Analisis Artificial Exoskeleton pada Prajurit TNI - Salam, Rudi; Iqbal, Mohammad; Hasanuddin, Iskandar (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
Soldier’s activities resulted in too much workload received by the body, especially in the back and waist. These conditions produce a high risk of musculoskeletal disorders especially if conducted continuously. The soldiers must carry a backpack containing supplies during training weighing up to 40 kg on average. All activities are conducted manually until the training is finish. Thus, the purposes of this study are to reduce spinal injury by identifying factors resulting from lifting loads that exceed the limits of the body, calculate the maximum load limit that can be carried by a soldier, and produce artificial exoskeleton as a tool for the Indonesian Armed Forces. The study used anthropometry, biomechanics, and physiological approach in solving the problem. The results show that the safe load can be carried by the soldiers is 30.46 kg. The body parts that feel the complaint are the upper neck, back, shoulder, buttocks. In addition, this study can produce a design of an artificial exoskeleton with the following dimensions: chest thickness 23 cm, chest width 32 cm, back length 52 cm. The soldiers can increase the force load by 9% of the initial weight of the load using this design.